2016
DOI: 10.1001/jamaoto.2015.3592
|View full text |Cite
|
Sign up to set email alerts
|

Four-Duct Ligation for the Treatment of Sialorrhea in Children

Abstract: The 4-duct ligation procedure offers a simple, effective, and minimally invasive approach to the management of sialorrhea in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Studies reviewed indicated surgical management of sialorrhoea is effective (Khadivi et al, ; Khan et al, ; Kok et al, ; Puraviappan et al, ; Stamataki et al, ; Stern et al, ). Unfortunately, apart from children with CP, there have been very few clinical studies based on patients with any other sialorrhoea‐related neurological disorders.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies reviewed indicated surgical management of sialorrhoea is effective (Khadivi et al, ; Khan et al, ; Kok et al, ; Puraviappan et al, ; Stamataki et al, ; Stern et al, ). Unfortunately, apart from children with CP, there have been very few clinical studies based on patients with any other sialorrhoea‐related neurological disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, apart from children with CP, there have been very few clinical studies based on patients with any other sialorrhoea‐related neurological disorders. Side effects were also reported, such as ranula, sialoadenitis, transient swelling of the mouth floor, pneumonia and operative urinary retention (Khadivi et al, ; Khan et al, ; Kok et al, ; Puraviappan et al, ). Dry mouth and dental caries were also reported in one study (Stern et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations